Enhanced voiding in Cu-Sn micro joints. (June 2022) - Njuki, M.; Thekkut, S.; Sivasubramony, R.; Greene, C.M.; Shahane, N.; Thompson, P.; Mirpuri, K.; Borgesen, P.; Dimitrov, N.
Highlights: The voiding tendency in 2.5/3D assembly joints is higher than that in larger BGA joints. The voiding level in micro joints is very sensitive to the peak reflow temperature. Repeated reflows promote the nucleation of more voids on any kind of electroplated Cu. The voiding tendency is more manageable at lowered post-reflow annealing temperatures. Abstract: The sporadic formation of Kirkendall voids in 300–500 μm thick solder joints on electroplated Cu pads has been shown to be related to the quality of the Cu and systematic studies eventually led to approaches for testing and preventing it. However, recent results suggested that the propensity for voiding is much higher in micro-joints with thicknesses below 25–30 μm. The present work confirms the higher voiding tendency at scales typical of 2.5/3D assemblies and reveals important differences in systematic trends between micro- and larger joints. The voiding still increases as the intermetallic layers grow over time after the reflow but, unlike for larger joints, the voiding level corresponding to a given Cu3 Sn thickness is very sensitive to both the peak reflow temperature and the subsequent thermal history. Another important difference is that the voiding is strongly enhanced by multiple reflows making it a particular concern in 3D assembly. Graphical abstract: Image, graphical abstract